Training on Diversification of Banana and Taro Food into Healthy Food Products with Economical Value in Bungus Barat Village, Padang City - Desy Kurniawati (Fakultas MIPA Universitas Negeri Padang, 2021)
In West Bungus Village, there are abundant bananas and taro crops. So far, bananas and taro have not been processed into nutritious healthy food products with economic value. This condition becomes a problem that needs to be found as a solution. if bananas and taro can be processed further, the selling value will be higher. From the situation analysis, the people of West Bungus Village need to be equipped with the knowledge on how to process bananas and taro into healthy nutritious foods that have economic value. Banana and taro processing techniques can be applied through education and training on the application of Applied Chemistry. This activity has had a positive impact, which has increased the knowledge and skills of the people of West Bungus Village in processing bananas and taro into alternative food sources and nutritious foods that have marketable economic value.